2020
DOI: 10.3389/fpsyg.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Organizational Behavior: Implications for Workplace Productivity and Safety

Abstract: The interaction between sleep and work-related behaviors influence many aspects of employee performance, safety, and health as well as organizational-level success. Although it is well established that quantity and quality of sleep can affect different types of task performance and personal health, the interactions between sleep habits and organizational behaviors have received much less attention. It is important to examine how sleep habits and workplace behaviors relate and the role of the underlying circadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 139 publications
0
37
0
1
Order By: Relevance
“…To further validate our findings, we suggest that convergent validity is established by comparing our measure and findings with objective measures such as actigraphy ( Sadeh, 2011 ) or results on psychomotor-vigilance task ( Wilkinson and Houghton, 1982 ) that are frequently used in order to objectively measure sleep and its effects ( Loh et al, 2004 ). Our study measured potential cumulative effects based on theoretical propositions and research placed forward by organizational researchers that suggest both sleep quantity and quality play an important role in ensuring self-regulation, as well as optimal states, behaviors, and attitudes at work ( Barnes, 2012 ; Crain et al, 2018 ; Pilcher and Morris, 2020 ). It does not, however, differentiate between the effects of sleep on workdays vs. non-workdays, changes in sleep duration, and specific items on sleep quality, such as sleep fragmentation and nightmares in investigating its effects on psychological functioning at work.…”
Section: Discussionmentioning
confidence: 99%
“…To further validate our findings, we suggest that convergent validity is established by comparing our measure and findings with objective measures such as actigraphy ( Sadeh, 2011 ) or results on psychomotor-vigilance task ( Wilkinson and Houghton, 1982 ) that are frequently used in order to objectively measure sleep and its effects ( Loh et al, 2004 ). Our study measured potential cumulative effects based on theoretical propositions and research placed forward by organizational researchers that suggest both sleep quantity and quality play an important role in ensuring self-regulation, as well as optimal states, behaviors, and attitudes at work ( Barnes, 2012 ; Crain et al, 2018 ; Pilcher and Morris, 2020 ). It does not, however, differentiate between the effects of sleep on workdays vs. non-workdays, changes in sleep duration, and specific items on sleep quality, such as sleep fragmentation and nightmares in investigating its effects on psychological functioning at work.…”
Section: Discussionmentioning
confidence: 99%
“…It is more likely that the tendency for decline in SBP closer to death in men can be related to differences in cardio‐vascular differences between the sexes. It has for a long time been known that men have a lower survival rate than females after a diagnosis of dementia (Rizzuto et al, 2012 ) and there are differences in blood pressure development, cardio vascular disease, and myocardial incident of infarction between the sexes as they age (Albrektsen et al, 2016 ; Barrett‐Connor, 2013 ; Hestad, Engedal, Schirmer, et al, 2020 ). It is seen that there is an accelerated risk of myocardial infarction in young men compared to young women.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that blood pressure drops as people approach death (Delgado et al, 2018 ; Goodwin, 2018 ; Hestad et al, 2020 ). Delgado et al, among others, have demonstrated in people over the age of 60 that blood pressure begins a downward trajectory more than 10 years before death, with the steepest declines occurring 2 years prior to death (Delgado et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Sleep quality is associated with alertness and our response to environment and sleep quality have an impact on many aspects of employee behaviour within the workplace including alertness at work, error-making and absenteeism. 2 Economically driven studies have explored the impact of shift work rather than individual measures of sleep dysfunction on occupational outcomes such as absenteeism. 3,4 The sleep disorders of nurses have been reported as a risk factor for patient safety.…”
mentioning
confidence: 99%